Parental binge drinking and offspring's high school non-completion: A prospective HUNT survey and educational registry study. (1st January 2022) - Burdzovic Andreas, Jasmina; Torvik, Fartein Ask; Lund, Ingunn Olea
Abstract: Background: Alcohol-use disorders (AUD) in parents are associated with adverse outcomes in offspring. It is less known whether other forms of parental drinking such as binge drinking may also be a risk factor for offspring's outcomes – specifically, high school non-completion. Methods: These questions were examined in a sample of 3101 offspring ( M age = 16.1 , SD = 1.68; 49.5% girls) from 2510 2-parent families who participated in the Nord-Trøndelag Health Study in Norway (HUNT3; Young-HUNT3) in 2006–08 and were followed-up through the National Education Database (NUDB) until 2014. Associations between maternal and paternal binge drinking patterns as reported in HUNT during offspring's adolescence and offspring's subsequent high school completion were examined using logistic regression models while accounting for a comprehensive set of socio-demographic, parental, and offspring characteristics as assessed at HUNT baseline. Effect modifications of these putative associations by offspring characteristics were also explored. Findings: Approximately 1 in 6 offspring (13.6% girls, 21.1% boys) failed to graduate high school within the officially designated time period, while roughly 1 in 5 mothers (20.4%) and 1 in 2 fathers (51.2%) reported any binge drinking. Weekly or more frequent binge drinking in fathers was prospectively associated with more than doubled odds of high school non-completion in offspring; OR = 2.23, 95% CI = 1.50–3.31. This effect remained substantively identical after adjustment for all covariates (aOR = 2.20, 95% CI = 1.38–3.50) and uniform across offspring characteristics such as gender, academic orientation and performance, anxiety and depression, typical alcohol consumption, and witnessing parental intoxication as assessed at HUNT baseline. Conclusions: Weekly or more frequent binge drinking in fathers negatively affected high school graduation prospects in their offspring. Highlights: Binge drinking in fathers was prospectively associated with high school non-completion in offspring. Fathers' weekly or more frequent binge drinking (vs. none) doubled the odds of offspring's high school non-completion. Parental drinking outside of clinically-diagnosed disorders affects their children's educational outcomes.